The Role of Petronage in the Existence of the Temple of Ganjuran - Danang Bramasti (Graduate School of Institut Seni Indonesia Yogyakarta, 2015)
Ganjuran temple is a place of Catholic worship located in Yogyakarta. The temple had been built by Schmutzer family, a Dutch sugar mill owner, from 1927 until 1930 in the shape of a Hindu temple. However, after the temple was erected, it did not get the attention of Catholics that it was dirty. Finally it was neglected and became a playground for children. It was only in 1990, Father Tomo made the temple a pilgrimage site by creating a series of activities centered on the temple. This paper is dedicated to study the role of patron, the Schmutzers and Father Tomo in the existence of the Temple of Ganjuran in three steps. Firstly, it strives to explain why this Catholic place of worship was built in the shape of a Hindu temple. Secondly, it explains the social process by which the temple then had been forgotten for sixty years. Thirdly, it explains the social process by which the temple became a major Catholic pilgrimage site in Indonesia. This study utilizes the concept of patronage in the development of an artwork as the main framework (Becker, 2008). The methods of applied study are by examining documents, interviews with people involved with the temple and field observations. By treating Ganjuran temple as an artwork embedded in an ‘art world’, web of actors who contributed to the making of Ganjuran temple as a locus of religius and artistic action is made visible.